Hierarchical Porous Cellulosic Triboelectric Materials for Extreme Environmental Conditions. Issue 9 (8th July 2022) - Zhao, Jiamin; Zhang, Wanglin; Liu, Tao; Liu, Yanhua; Qin, Ying; Mo, Jilong; Cai, Chenchen; Zhang, Song; Nie, Shuangxi
Abstract: Synthetic polymer materials such as paraformaldehyde and polyamides are widely used in the field of energy engineering. However, they pose a challenge to environmental sustainability because they are derived from petrochemicals that are non‐renewable and difficult to degrade in the natural environment. The development of high‐performance natural alternatives is clearly emerging as a promising mitigation option. Inspired by natural bamboo, this research reports a "three‐step" strategy for the large‐scale production of triboelectric materials with special nanostructures from natural bamboo. Benefiting from the special hierarchical porous structure of the material, Bamboo/polyaniline triboelectric materials can reach short‐circuit current of 2.9 µA and output power of 1.1 W m –2 at a working area of only 1 cm 2, which exceeds most wood fiber‐based triboelectric materials. More importantly, it maintains 85% energy harvesting after an extreme environment of high temperature (200 °C), low temperature (−196 °C), combustion environment, and multiple thermal shocks (Δ T  = 396 °C). This is unmatched by current synthetic polymer materials. This work provides new research ideas for the construction and application of biomass structural materials under extreme environmental conditions. Abstract : Inspired by natural bamboo, this study reports a "three‐step" strategy for the mass production of cellulosic triboelectric materials with resistance to extreme environmental conditions. It achieves high triboelectric properties with a working area of only 1 cm 2 . More importantly, it can maintain 85% energy harvesting and meet diverse self‐powered induction even after resisting extreme environmental conditions.